THE IMPACT OF DIGITAL MARKETING STRATEGIES AND SOCIAL INFLUENCE IN THE CULINARY INDUSTRY: EVIDENCE FROM RICE BOWL CONSUMERS IN MAKASSAR - Hanisa Arcan Samawati; Mohamad Maruf Hasrul; Edric Aurelio Tan; Jennifer Diaz Almer Lisarib; Levina Chandra; Asriah Syam (Accounting Profession Journal (APAJI), 2026)
This study examines the effects of Social Media Marketing Content and Peer Influence on the purchase intention of rice bowl consumers in Makassar, with Attitude toward Advertising as a mediating variable. Using a quantitative approach, data were collected from 150 Gen Z respondents through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The study aims to explain how visually engaging content and social interaction influence consumer attitudes and purchasing decisions in a highly competitive culinary market. The findings provide practical insights for MSMEs in designing socially responsive digital marketing strategies.